Public-private partnerships for hospitals - Martin McKee; Nigel Edwards; Rifat Atun (The World Health Organization, 2006)
While some forms of public-private partnerships are a feature of hospital construction and operation in all countries with mixed economies, there is increasing interest in a model in which a public authority contracts with a private company to design, build and operate an entire hospital. Drawing on the experience of countries such as Australia, Spain, and the United Kingdom, this paper reviews the experience with variants of this model. Although experience is still very limited and rigorous evaluations lacking, four issues have emerged: cost, quality, flexibility and complexity. New facilities have, in general, been more expensive than they would have been if procured using traditional methods. Compared with the traditional system, new facilities are more likely to be built on time and within budget, but this seems often to be at the expense of compromises on quality. The need to minimize the risk to the parties means that it is very difficult to "future-proof" facilities in a rapidly changing world. Finally, such projects are extremely, and in some cases prohibitively, complex. While it is premature to say whether the problems experienced relate to the underlying model or to their implementation, it does seem that a public-private partnership further complicates the already difficult task of building and operating a hospital.